Arbuscular Mycorrhizal Fungi and Microbial Activity in Mine Tailings: Potential to Promote Plant Growth Under Stress Conditions - Hernández-Acosta, Elizabeth; Baeza-Guzmán, Yajaira; Trejo-Aguilar, Dora (REVISTA TERRA LATINOAMERICANA, 2025)
Mining facilities release considerable amounts of toxic elements into the environment, which persist for long periods of time, their remediation is necessary for human health. Arbuscular mycorrhizal symbiosis improves plant resistance to biotic and abiotic stress, and aids in the adsorption of nutrients under heavy metal stress. The present study aims to determine the mycotrophic plants established in mine tailings, their relationship with microbial activity, and with the physicochemical characteristics of mine tailings. A physical, chemical, and plant characterization of the mine tailings was carried out, and the percentage of mycorrhizal colonization, microbial activity, and concentrations of lead, cadmium, nickel, and zinc were evaluated. The results showed that the mine tailings had neutral pH, very low organic matter content, medium nitrogen content, high phosphorus and potassium content, low calcium availability, and medium magnesium availability. Eleven species were identified from nine families, four species were shrubs, three species were trees, three species were herbaceous, and one species was cactus; 10 of them are perennial. Colonization percentages ranged from 11 to 91%, and microbial activity values ranged from 6 to 42 µg p-nitrophenol g-1 dry soil. Concentrations of 10.63 mg kg-1 for lead, 0.58 mg kg-1 for cadmium, 0.20 mg kg-1 for nickel, and 36.21 mg kg-1 for zinc were found. The data obtained showed that the plants were colonized by arbuscular mycorrhizal fungi (AMF) and the rhizosphere zone had a wide range of microbial activity that could allow them to tolerate the stress conditions present in mine tailings.